2017
DOI: 10.1155/2017/6204742
|View full text |Cite
|
Sign up to set email alerts
|

Indian Classical Dance Classification with Adaboost Multiclass Classifier on Multifeature Fusion

Abstract: Extracting and recognizing complex human movements from unconstraint online video sequence is an interesting task. In this paper the complicated problem from the class is approached using unconstraint video sequences belonging to Indian classical dance forms. A new segmentation model is developed using discrete wavelet transform and local binary pattern (LBP) features for segmentation. A 2D point cloud is created from the local human shape changes in subsequent video frames. The classifier is fed with 5 types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 37 publications
1
15
0
Order By: Relevance
“…But real-time implementation of ICD identification demands a high-speed classifier. To improve the speed of the recognition, Adaboost classifier [14] is introduced. Even though the recognition is fast, the classification results were found to be somewhat unreliable at times.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…But real-time implementation of ICD identification demands a high-speed classifier. To improve the speed of the recognition, Adaboost classifier [14] is introduced. Even though the recognition is fast, the classification results were found to be somewhat unreliable at times.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we approached the problem with SVM classifier [13] on dance videos and found that only multiclass SVMs should be considered. The average recognition rates obtained in implementing Adaboost [14], Artificial Neural Networks (ANN) [15], deep ANN [16], and adaptive graph matching (AGM) [17] on dance data are not up to the mark.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…To further know the robustness and efficiency of flower image classification with the proposed CNN, it is compared with other classifiers. For faster recognition, we used Adaboost classifier [40] and ended with a very low classification rates. Further, we replaced Adaboost with a traditional artificial neural network (ANN) [35] [36] [37] [38] for flower image classification and found better recognition rates.…”
Section: Cnn Training and Testing With Different Dataset In Various Bmentioning
confidence: 99%
“…In [1] SVMC is firstly introduced and verified with set of benchmark dataset of image and it is used in this work and they yield a major furtherance new fusion model and result outcome is based on qualitative and quantity n datasets. There is major investigation is carried out in [2] about shapes and large pixel size of image which is taken into account by using a algorithm of segmented interactive classifier and in this present proposed work used this technology for accurate and sharp identification images in the sets. The new superior computer vision model [3] is yield with aim to help for e-learning and self learning.…”
Section: Introductionmentioning
confidence: 99%